AI-Ghazālī’s Ṣūfīsm: A Critical Appraisal - Zaroug, Abdullahi Hassan (Intellectual Discourse, 2013)
This paper aims at investigating al-Ghazālī’s ideas on ṣūfīsm, including his epistemological, ethical, philosophical and spiritual views. It analyses and evaluates al-Ghazāli's views on kashf, ecstatic utterances, the criteria for judging ecstatic utterances, virtues and vices, free will, fate and divine decree seclusion, intention, states and stations such as asceticism, love and contentment. The paper also discusses the question of which methodology is appropriate for investigating mystical phenomena, and whether it is possible for a non-ṣūfī to have access to the sūfī world. Furthermore, the paper attempts to show that much can be gained from Sunni taṣawwuf, which al-Ghazālī may be considered to represent, since he emphasizes the importance of spiritual deeds, and that worship must be accompanied by internal states such as good intentions and sincerity. Al- Ghazālī also emphasizes the importance of morality, contributes greatly to moral psychology i. e., mechanism of the soul, and shows remarkable insight into the diagnosis and treatment of the illnesses of the soul.